Contextualizing negative attitudes to wildlife and wildlife governance in the moral economy of Swedish farmers - Larsson, Simon; Larsson, Susanna Olivia; Bennett, Juliana; Sjölander-Lindqvist, Annelie (Frontiers in Conservation Science, 2022)
Conflicts over managing large carnivores have been prominent in Sweden in recent decades. The most significant controversies are related to wolves, but the bear, lynx, and wolverine are also included. While the state and environmental organizations make efforts to guarantee a viable population of the large protected carnivores, farmers generally have a negative attitude towards large carnivores and a low level of trust in wildlife governance. Based on 22 in-depth interviews, 37 telephone questionnaires with Swedish farmers, and an analysis of 111 applications for protective hunting, this paper aims to demonstrate how these farmers' perspectives on large carnivores can be explained by moral (sense of right and wrong) and moral economy (a system of obligations related to values and relations intervening with political views and financial decisions). The paper argues that farming, in addition to being an economic activity, is integrated with values, heritage, and relations to other human beings and animals. Farmers understand these values to be threatened by large carnivores, especially by wolves. The paper contextualizes negative sentiments, conflicts, protests, and also illegal hunting of large carnivores in relation to a sense of morals, sense of fairness, meanings, traditions, and mechanisms of daily life. We argue that this perspective provides a lens through which to interpret the conflict between farmers on the one side and the state and animal rights activists on the other. Such interpretation has consequences for understanding the legitimacy of government, shifting the focus from the processes of political governance (predominant in liberal political philosophy) to legitimacy tied to collective notions of social goods.